Influence of redox processes on the antioxidant activity of the symbiotic starter biomass - G. A. Donskaya; L. G. Krekker (Пищевые системы, 2023)
The biological system of the  microbial antioxidant protection is a subject of a certain level of the  physiological oxidative process. To prevent oxidation, a regulator of intracellular metabolism, tripeptide glutathione, is accumulated in cells. Glutathione is very important for the  antioxidant response and maintenance of intracellular redox potential. Its role in several  metabolic adaptive symbiotic processes of yeasts  and lactic acid bacteria is not completely elucidated and is of scientific and practical interest. Glycine is a component of the polypeptide chain and substances that form the  primary structure of glutathione. The aim of this  study  was to determine an effect of the redox processes on the antioxidant activity through regulation of the level of the glutathione constituent, glycine, in a nutrient medium to obtain the microbial biomass of the multicomponent starter culture. As a result of the  performed investigations, a direct dependence between the  antioxidant activity calculated by the  coulometric method and  concentration of glycine  introduced into  the  nutrient medium was determined. It has  been established that addition of 0.2–0.8% of glycine leads to a decrease in the redox potential. The results reflected in this publication show that the process of the development of aerobic  microorganisms in the presence of reducing substances occurs  quite  actively. The number of yeasts  increased from 1.6· 104  to 3.6· 105  CFU/g during 24-hour incubation. An increase in glycine  from  0.5 to 0.8% enhanced the  development of both  anaerobic and  aerobic microorganisms. It has been  found  that an increase in the  glycine  concentration from  0.8% to 1.5% shifted the process toward  the oxidative metabolism; an amount of reduced glutathione in the culture liquid increased practically twofold, while the concentration of oxidized glutathione in the test  sample was in a range  of 0 to 5%. This allows regarding glutathione as a potential regulator of the  redox  processes and antioxidant activity of biomass of lactic acid bacteria and yeasts.